Sulfina, 2021PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI MANFAAT TERHADAP MINAT UNTUK MENGGUNAKAN UANG ELEKTRONIK (Shopeepay) - Sulfina (2021)
This study is a quantitative study that aims to determine the effect of perceived ease of use and perceived benefits on interest in using electronic money (ShopeePay). The population in this study are people who are in the JABODETABEK area. The sample taken in this study amounted to 100 using non-probability sampling technique and purposive sampling method. Data collection is done by distributing questionnaires through google forms, and processing the data using SmartPLS. The results of the test showed that the perceived ease of use variable had a positive and significant effect on interest in use of 0.507, the perceived benefit variable had a positive and significant effect on interest in use of 0.444 and obtained a determinant coefficient value of 86.9%.